2022
DOI: 10.3389/fimmu.2022.1006996
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 signaling modulates the immune response induced after antigen targeting to conventional type 1 dendritic cells through the DEC205 receptor

Abstract: Conventional dendritic cells (cDC) are a group of antigen-presenting cells specialized in priming T cell responses. In mice, splenic cDC are divided into conventional type 1 DC (cDC1) and conventional type 2 (cDC2). cDC1 are specialized to prime the Th1 CD4+ T cell response, while cDC2 are mainly associated with the induction of follicular helper T cell responses to support germinal center formation. However, the mechanisms that control the functions of cDC1 and cDC2 are not fully understood, especially the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Instead, TNF-α secretion, but not IL-1β, was significantly decreased ( Figure 7B ). Interestingly, the reduced phosphorylation of STAT3, which is activated by many cytokines active in inflammation, including IL-6, IL-10, IL-11, and IL-21, suggests impaired cytokine signaling upon HDAC1-3 inhibition ( Sulczewski et al., 2022 ) ( Figure 7C ).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, TNF-α secretion, but not IL-1β, was significantly decreased ( Figure 7B ). Interestingly, the reduced phosphorylation of STAT3, which is activated by many cytokines active in inflammation, including IL-6, IL-10, IL-11, and IL-21, suggests impaired cytokine signaling upon HDAC1-3 inhibition ( Sulczewski et al., 2022 ) ( Figure 7C ).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, we have used antigen targeting to DCs to study in more detail their signaling pathways. We have shown that the canonical signal transducer and activator of transcription 3 (STAT3) pathway regulates the capacity of cDC1s to support CD4+ T cell responses after antigen delivery to the DEC205 receptor, 45 while the STAT6 pathway controls B cell positioning in the germinal centers after antigen delivery to the DCIR2 receptor. 46 Proteins derived from other protozoans have also been targeted to cDCs in vivo.…”
Section: Delivery Of Clinically Relevant Antigens To Dcsmentioning
confidence: 99%
“…HDAC6 displays many of its immune-related effects by affecting the STAT3 signaling pathway, which is involved in the development of malignancies and in the induction and maintenance of immune tolerance and inhibition of immune responses [ 46 , 137 ]. STAT3 signaling can be activated with cytokines IL-6, IL-10, IL-21, and TNF that in DCs downregulate the expression of MHC class II and costimulatory molecules, thereby inducing the tolerogenic immune response [ 138 ]. Furthermore, STAT3 plays a key role in suppressing signal transduction mediated by Toll-like receptors (TLRs) in mature phagocytic cells.…”
Section: Roles Of Hdac6 In Physiological Processesmentioning
confidence: 99%